New insights into the structure domain and function of NLR family CARD domain containing 5 - Haiqing Zhu; Chengwei Xiao; Jiahua Chen; Bao Guo; Wenyan Wang; Zhenhai Tang; Yunxia Cao; Lei Zhan; Jun-hui Zhang (Cell Communication and Signaling)
Abstract NOD-like receptor family CARD domain-containing 5 (NLRC5) is a major transcriptional coactivator of MHC class I genes. NLRC5 is the largest member of the NLR family and contains three domains: an untypical caspase recruitment domain (uCARD), a central nucleotide-binding and oligomerization domain (NOD or NACHT), and a leucine-rich repeat (LRR) domain. The functional variability of NLRC5 has been attributed to its different domain interactions with specific ligands in different cell types. In this review, we address the molecular mechanisms and their implications in multiple microenvironments based on the different functional domains of NLRC5.